Translational Research in Europe for the Assessment and Treatment for Neuromuscular Disorders (TREAT-NMD) - Leary, Rebecca; Oyewole, Anne O.; Bushby, Katharine; Aartsma-Rus, Annemieke (Neuropediatrics, 2017)
Translational research in Europe for the assessment and treatment of neuromuscular disorders (TREAT-NMD) is a global network of world-class experts within the neuromuscular community whose mission is to support all stages of therapy development and improve the health and quality of life of people around the world with neuromuscular disorders (NMD). Since 2007, TREAT-NMD has played a central role in bringing together the right experts, patients, advocacy organizations, scientists, healthcare professionals, and pharmaceutical companies. By uniting these experts within the neuromuscular community, TREAT-NMD has supported preclinical research in animal and cell models that has raised the potential for clinical trials. TREAT-NMD has successfully developed several key resources, including cell and animal standard operating protocols (preclinical research), global patient registries, ethical framework and care guidelines, and family guides, to help develop and extend translation research in the field, thereby making the field ready for clinical trials. This review aims to highlight key achievements of the network, which spans a decade and the successful partnership with our stakeholders who have enabled the field to identify and address challenges to therapeutic development and standard of care for patients. This review will also outline future perspectives.
Keywords: TREAT-NMD; neuromuscular disorders; translational research; muscular dystrophy; therapy